Developmental exposures to perfluorooctanesulfonic acid (PFOS) impact embryonic nutrition, pancreatic morphology, and adiposity in the zebrafish, Danio rerio. (15th April 2021) - Sant, Karilyn E.; Annunziato, Kate; Conlin, Sarah; Teicher, Gregory; Chen, Phoebe; Venezia, Olivia; Downes, Gerald B.; Park, Yeonhwa; Timme-Laragy, Alicia R.
Abstract: Perfluorooctanesulfonic acid (PFOS) is a persistent environmental contaminant previously found in consumer surfactants and industrial fire-fighting foams. PFOS has been widely implicated in metabolic dysfunction across the lifespan, including diabetes and obesity. However, the contributions of the embryonic environment to metabolic disease remain uncharacterized. This study seeks to identify perturbations in embryonic metabolism, pancreas development, and adiposity due to developmental and subchronic PFOS exposures and their persistence into later larval and juvenile periods. Zebrafish embryos were exposed to 16 or 32 μM PFOS developmentally (1–5 days post fertilization; dpf) or subchronically (1–15 dpf). Embryonic fatty acid and macronutrient concentrations and expression of peroxisome proliferator-activated receptor (PPAR) isoforms were quantified in embryos. Pancreatic islet morphometry was assessed at 15 and 30 dpf, and adiposity and fish behavior were assessed at 15 dpf. Concentrations of lauric (C12:0) and myristic (C14:0) saturated fatty acids were increased by PFOS at 4 dpf, and PPAR gene expression was reduced. Incidence of aberrant islet morphologies, principal islet areas, and adiposity were increased in 15 dpf larvae and 30 dpf juvenile fish. Together, these data suggest that the embryonic period is a susceptible window of metabolic programming in response to PFOS exposures, and that these early exposures alone can have persisting effects later in the lifecourse. Graphical abstract: Image 1 Highlights: PFOS increased embryonic saturated fatty acids and decreased PPAR gene expression. Developmental PFOS exposures increased pancreatic islet areas at 15 and 30 dpf. Developmental PFOS exposures increased lipid staining and the number of lipid droplets. No significant behavioral changes were observed at 15 dpf due to PFOS exposures.